EXPLORING FIRST YEAR UNIVERSITY STUDENTS’ STATISTICAL LITERACY: A CASE ON DESCRIBING AND VISUALIZING DATA - Ezra Putranda Setiawan; Heru Sukoco (Journal on Mathematics Education, 2021)
Statistical literacy, which is the ability to use statistics in daily life, is an essential skill for facing society 5.0. This study aims to explore first-year university students’ ability to properly use simple descriptive statistics and data visualization. Qualitative data were collected using a set of questions from 39 undergraduate students. Many students were able to calculate various descriptive statistics, but some of them were still unable to determine suitable statistics to describe the data clearly. Related to data visualization, many students failed to provide a meaningful chart that effectively shows the difference between two groups of data. Students with higher statistical literacy tend to use comparison or variability reasoning to determine the usage of descriptive statistics, and use data-based reason in visualizing the data. Improvement in statistical teaching – both in the university and the secondary school – is needed so that the students can use descriptive statistics and data visualization correctly.